Alternativas ecológicas de manejo da mosca-negra e de ácaros no polo citrícola de Sergipe e Bahia - Dias, Karoline Louise Lima (2024)
The main citrus production area in the Northeast region of Brazil includes southern Sergipe and the northern coast of Bahia. In this region, the attack of pests such as the citrus blackfly, Aleurocanthus woglumi (Hemiptera: Aleyrodidae); the Texas citrus mite, Eutetranychus banksi (Acari: Tetranychidae); and the citrus rust mite, Phyllocoptruta oleivora (Acari: Eriophyidae) results in low yields in orchards. Thus, the aim of this study was to evaluate the toxicity of cottonseed oil to A. woglumi and E. banksi, as well as the toxicity of the oil and a lime-sulfur solution to P. oleivora. In this study, the lethal concentrations (LC) of fixed cottonseed oil for blackfly nymphs were first determined under laboratory conditions. Subsequently, the efficiency of fixed cottonseed oil in controlling blackfly was evaluated in an experimental orange orchard. Although the LC estimates were conducted for blackfly, the efficiency of cottonseed oil in controlling Texas citrus mite was also evaluated since the mite occurred concomitantly with blackfly in the experimental orchard. The results of this study showed that fixed cottonseed oil was toxic to blackfly under laboratory conditions. This oil was likewise effective in reducing the populations of blackfly and Texas citrus mite under field conditions. Furthermore, the lethal concentrations (LC) of fixed cottonseed oil for adult citrus rust mites were determined, and the effect of lime sulfur on the mite was evaluated due to the high potential of these products in controlling phytophagous mites. The results showed that both cottonseed oil and the lime-sulfur solution have potential in controlling the citrus rust mite. In conclusion, fixed cottonseed oil is an effective alternative for managing citrus blackfly and Texas citrus mite in the citrus growing region of Sergipe and Bahia. Additionally, the toxicity of the cottonseed oil and lime-sulfur solution showed promise in control of citrus rust mite.